2019
DOI: 10.1088/1755-1315/290/1/012150
|View full text |Cite
|
Sign up to set email alerts
|

Potted Plants as Active and Passive Biofilters Improving Indoor Air Quality

Abstract: Plants are the planet’s source of oxygen and the sink that removes carbon dioxide produced by burning, respiration and decay of organisms. The studies performed in small chambers indicated that plants also reduce volatile organic compounds (VOC’s). All these phenomena result in a fact that potted plants have a potential to improve IAQ and to some extent to support ventilation. Trends to “go green” increase the growing interest in the introduction of a large number of plants to offices. One should remember that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…They conducted a test to measure the concentration of carbon dioxide in offices using snake plants. Sowa et al ( 2019) also proved the ability of potted plants to purify Indoor Air Quality. They found that VOC, formaldehyde were reduced to higher extend as compared to the same procedure performed without plants.…”
Section: Indoor Air Phytoremediation Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…They conducted a test to measure the concentration of carbon dioxide in offices using snake plants. Sowa et al ( 2019) also proved the ability of potted plants to purify Indoor Air Quality. They found that VOC, formaldehyde were reduced to higher extend as compared to the same procedure performed without plants.…”
Section: Indoor Air Phytoremediation Methodsmentioning
confidence: 89%
“…Many researchers proved that plants have the special ability to reduce the fatigues, stress, mood alterations.Another significant advantage of the plant is the ability to provide cooling effect due to evaporation. Potted plants have also the ability to remove VOCs and formaldehyde ( Sowa et al, 2019). The above-ground part of the plant, roots and microorganisms found in the substrate are important mechanisms which help to reduce the concentration of indoor Following are the brief discussions on Sansevieria laurentii (Mother-in-law tongue).…”
Section: Indoor Air Phytoremediation Methodsmentioning
confidence: 99%
“…Through photosynthesis, plants use light as an energy source to fix CO 2 in the form of carbohydrates and release O 2 into the atmosphere (Sowa et al, 2019). In the same environment, plants with a high photosynthetic rate showed more effective CO 2 removal than plants with a low photosynthetic rate.…”
Section: Resultsmentioning
confidence: 99%
“…For respiratory comfort, the application of Nephrolepis exaltata Bostoniensis on the green wall was observed to have removed 0.3 to 0.5 PM levels, thereby leading to 45.78% and 92.46% improvement in IAQ [16]. Moreover, the addition of a potted plant in the building interior was reported to have reduced Volatile Organic Compound (VOC) and formaldehyde levels by 48% and 145%, respectively [36].…”
Section: Figure 1 Type Of Biowallmentioning
confidence: 99%